2008
DOI: 10.1111/j.1743-6109.2008.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy Assessment of Tamsulosin vs. Tamsulosin Plus Tadalafil in the Treatment of LUTS/BPH. Pilot Study

Abstract: Introduction The high incidence of erectile dysfunction (ED) and lower urinary tract symptoms (LUTS) in aging men and the same pathophysiology make probable to treat both disorders with the same treatment. Numerous authors evaluated the actions of PDE5i in improving the LUTS/(benign prostate hyperplasia) BPH. Aim To assess the efficacy and safety of tamsulosin 0.4 mg/day vs. tamsulosin 0.4 mg/day plus tadalafil 20 mg/day in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
114
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 44 publications
(72 reference statements)
12
114
1
4
Order By: Relevance
“…29 Supporting this is that the baseline Qmax of 14.54 ± 3.26 ml s À1 in the present study is high compared with those recorded in previous studies. [23][24][25][26] In comparison with Kaplan et al and Tuncel et al, the full dose of mirodenafil, which we used might result in similar outcomes of improvement for LUTS despite only two times per week. In addition, we investigated two groups to examine correlation on improvement of IIEF-5 and IPSS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…29 Supporting this is that the baseline Qmax of 14.54 ± 3.26 ml s À1 in the present study is high compared with those recorded in previous studies. [23][24][25][26] In comparison with Kaplan et al and Tuncel et al, the full dose of mirodenafil, which we used might result in similar outcomes of improvement for LUTS despite only two times per week. In addition, we investigated two groups to examine correlation on improvement of IIEF-5 and IPSS.…”
Section: Discussionmentioning
confidence: 57%
“…Alfuzosin alone also significantly improved the Qmax (11.7%, P ¼ 0.03) but the combination therapy was even better (21.1%, P ¼ 0.02). Another study on the efficacy of PDE5i/a 1 -blocker combination therapy for LUTS/BPH was that by Bechara et al, 24 who performed a study with 27 BPH patients who had had LUTS for X6 months to examine the efficacy of tamsulosin 0.4 mg OAD monotherapy and tamsulosin 0.4 mg and tadalafil 20 mg OAD combination therapy. The treatment started with the monotherapy or combination therapy for 45 days, after which the therapy was switched to the other regimen for another 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…9 This combination had also been used for the treatment of lower urinary tract symptoms associated with benign prostatic hyperplasia by Bechara et al and has shown significant improvements in pain by the relaxation of the bladder, urethra, and prostate and was the basis of this pilot study. 10 In another study conducted by Bos et al titled, 'update on medical expulsive therapy for distal ureteral stones: beyond alpha-blockers' concluded that corticosteroid therapy in adjunct to alpha-blocker therapy is effective in improving expulsion rates. PDE5 inhibitors did not show significantly higher expulsion rates compared to alpha-blockers and calcium channel blockers remain inferior to alpha-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several types of a 1 -AR antagonists have been reported, such as tamsulosin (4,5), BMY-7378 (3,6), prazosin (3,(7)(8)(9)(10) and spiperone (3) (Figure 1). These antagonists, albeit diverse in their structures, have two common structural features (11).…”
mentioning
confidence: 99%